Age-related differences in neural activity for novelty and relational encoding of scenes - Leow, Wei Yang Dayton (2015)
Episodic memory decline is a hallmark of the aging brain. Episodic encoding can be delineated into novelty (processing the unfamiliarity) and relational (processing the meaningfulness) encoding. Present literature has shown the fusiform gyrus (FG), hippocampus, parahippocampus and inferior frontal gyrus (IFG) are involved in relational encoding of scenes; while the inferior occipital gyrus (IOG) is additionally involved in novelty encoding of scenes - serving as viable regions of interest (ROIs) when examining the neural correlates of novelty and relational encoding of scenes. Age-related fMRI studies have reported that older adults show contralateral prefrontal recruitment during episodic encoding – presented as the hemispheric asymmetry reduction in older adults (HAROLD) model. A contralateral prefrontal recruitment may suggest an increased functional connectivity (FC) between the left and right prefrontal regions. However, the use of FC analysis to support the HAROLD model is currently lacking in present literature. Furthermore, age-related studies on episodic encoding have not examined if novelty and relational encoding are differentially affected by age. Hence, it will be informative to evaluate if the HAROLD effect is evident for novelty and relational encoding. This study utilized a fMRI task sensitive to both novelty and relational encoding of scenes to investigate age-related differences in the functional connectivity (FC), focusing on a priori ROIs, with the HAROLD effect being predicted. [2nd Award]